Microbial contamination of preservative free eye drops in multiple application containers. Issue 2 (19th January 2006) - Rahman, M Q; Tejwani, D; Wilson, J A; Butcher, I; Ramaesh, K
Abstract : Background/aims: The majority of eye drops used in the United Kingdom contain preservatives and are bottled in plastic containers. Preservative free drops are used to avoid ocular irritation and allergies in certain individuals. The aim of this study was to investigate the incidence of microbial contamination of preservative free drops dispensed from multiusage containers. Methods: Eye drop bottles were collected from patients attending the Tennent Institute of Ophthalmology outpatient and inpatient departments. The bottles were collected on day 3 (for inpatients) and day 7 (for outpatients) of use. The drops were inoculated onto different culture plates (chocolate agar, blood agar, fungal culture media, and enriched media) and the resulting microbial growth was identified using standard microbial identification techniques. Results: 95 eye drop bottles were collected, containing a variety of 10 different eye drops. Significant bacterial growth was found in eight bottles. In total, seven different types of organism were identified from the eye drops. The organisms identified were Staphylococcus aureus, coagulase negative staphylococcus, Bacillus spp, Serattia spp, Klebsiella oxytoca, Enterobacter cloacae, and alpha streptococcus. Staph aureus was the commonest microbial organism. Conclusion: Preservative free eye drops in multiple application containers are at risk of contamination by potentially pathogenic micro-organisms.